Antarctica's vegetation in a changing climate. (16th November 2022) - Colesie, Claudia; Walshaw, Charlotte V.; Sancho, Leopoldo Garcia; Davey, Matthew P.; Gray, Andrew
Abstract: Antarctica plays a central role in regulating global climatic and oceanographic patterns and is an integral part of global climate change discussions. The functioning of Antarctica's terrestrial ecosystems is dominated by poikilohydric cryptogams such as lichens, bryophytes, eukaryotic algae, and cyanobacteria and there are only two native species of vascular plants. Antarctica's vegetation is highly adapted to the region's extreme conditions but, at the same time, it is potentially highly susceptible to climatic fluctuations. Biological responses to shifts in temperature, water availability, wind patterns, snow, and ice cover are complex, taxa‐specific and act on different temporal and spatial scales. In maritime Antarctica, where warming and mass loss of outlet glaciers have been mainly observed, the vegetation is expected to show increases in productivity, abundance, and cover. In continental Antarctica, observational and experimental evidence is still sparse, but it is pointing toward even drier and harsher conditions for survival. We need more information on what the observed and predicted changes in Antarctic vegetation are for different regions and ecosystems. This will inform us how environmental change and human impact will shape the future of these ecosystems, and whether the speed and magnitude of change have habitat‐specific effects and implications. Antarctica's unique ecosystems are changing and in this review, we describe the current situation, tools to measure, and evaluate change and how change is likely to look in the future. This article is categorized under: Climate, Ecology, and Conservation > Observed Ecological Changes Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change Climate, Ecology, and Conservation > Modeling Species and Community Interactions Assessing Impacts of Climate Change > Observed Impacts of Climate Change Abstract : Antarctica's unique terrestrial ecosystems are changing with significant impact on the local vegetation. Change is manifold and includes alterations in abiotic and biotic interactions. How the vegetation will respond is still unclear.